Crisis on the terrain of language. - Heller, Monica (Anthropologica, 2023)
This text explores the role of language in times of crisis and social change, highlighting its connection to power dynamics and social justice. It discusses how language can be destabilized and questioned, leading to a reevaluation of what is considered legitimate language and who can be seen as a legitimate speaker or hearer. The text also examines the relationship between language and power, particularly in the context of nation-states and the inequalities that exist within and between them. It concludes by discussing contemporary examples, such as the use of terms like "fake news" and "wokeness," and the Occupy movement, as efforts to challenge existing power structures and create more inclusive discursive spaces. Additionally, the text explores responses to the global spread of English and the control of global communication, as well as the use of language in imagining alternative worlds. Overall, the text emphasizes the complexities and contradictions inherent in language and its role in shaping our understanding of the world and who belongs in it.